Лыз яг: повестьёс но веросъёс / Пётр Чернов - Чернов Петр Константинович (Удмуртия, 1991)
Экземпляры: ф.2 (1991) / Инвентарный номер: 27596 / Цена: 1.60 / Авт.знак: Ч-49 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)